Clinical and Electrocardiographic Predictors of Heart Failure in Patients Presenting with Long-Standing Hypertension - Huma Naeem Tareen, Muhammad Rehan Khan, Ghazala Shaheen, Muhammad Ali Khawaja, Iftikhar Hussain, Zeeshan Faisal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the greatest risk factors of heart failure development is long-term hypertension because of structural and electrical remodelling of the myocardium. Simple clinical and electrocardiographic parameters that predict risk of patients in the early stages of at-risk might prevent the onset of overt heart failure. Methods: The study was a descriptive cross-sectional study carried out in the Department of Cardiology, Lahore Medical and Dental College, from 03-01-2023 to 04-07-2023. One hundred and eighty patients who had a history of hypertension of five years or more and were 30 years of age and above were recruited. Standard 12-lead electrocardiography and clinical assessment was conducted to establish the predictors of heart failure. Data were assessed with the SPSS 26. Results: There were 42.2% of patients with heart failure. Poor blood pressure regulation, diabetes mellitus, and obesity were found to be significantly linked with heart failure; furthermore, age, and the long period of hypertension were also found to be significantly linked with heart failure. Electrocardiogram results, including left ventricular hypertrophy, left atrial enlargement, increased QRS, ST-T wave alteration, and atrial fibrillation, were significantly more common in the heart failure patients. Conclusion: Patients with chronic hypertension have the prevalence of heart failure. Clinical and electrocardiographic evaluation is a pragmatic method of early detection of high-risk patients and could help to intervene in time and limit the disease progression. Keywords: Hypertension; heart failure; Electrocardiography; Clinical predictors.